Frequency, patchiness and intensity of tropical savanna fires: analysis using field data and remote sensing - Oliveira, Sofia Luísa de Jesus (2014)
Doutoramento em Engenharia Florestal e dos Recursos Naturais - Instituto Superior de Agronomia